Synthesis of novel piperazinyl triazolo cyclobutane nucleoside analogues - Thủy, Trần Thị Thu; Thắng, Ngô Ngọc; Hà, Đinh Thị; Chiến, Nguyễn Quyết; Legoupy, Stephanie (Vietnam Journal of Chemistry, 2014)
The Huigen azide-alkyne cycloaddition was used as key step for the synthesis of  new piperazinyl-triazolo-cyclobutene derivatives from the azido-methylenylcyclobutene intermediate in good yields. Dihydroxylation following by desilylation on these compounds provides four new enantiomerically enriched triazolo-cyclobutane nucleoside analogues.